Comparison of trout hepatocytes and liver S9 fractions as in vitro models for predicting hepatic clearance in fish. (25th August 2016) - Fay, Kellie A.; Fitzsimmons, Patrick N.; Hoffman, Alex D.; Nichols, John W.
Abstract: Isolated hepatocytes and liver S9 fractions have been used to collect in vitro biotransformation data for fish as a means of improving modeled estimates of chemical bioaccumulation. To date, however, there have been few direct comparisons of these 2 methods. In the present study, cryopreserved trout hepatocytes were used to measure in vitro intrinsic clearance rates for 6 polycyclic aromatic hydrocarbons (PAHs). These rates were extrapolated to estimates of in vivo intrinsic clearance and used as inputs to a well stirred liver model to predict hepatic clearance. Predicted rates of hepatic clearance were then evaluated by comparison with measured rates determined previously using isolated perfused livers. Hepatic clearance rates predicted using hepatocytes were in good agreement with measured values (<2.1‐fold difference for 5 of 6 compounds) under 2 competing binding assumptions. These findings, which may be attributed in part to high rates of PAH metabolism, are similar to those obtained previously using data from liver S9 fractions. For 1 compound (benzo[ a ]pyrene), the in vivo intrinsic clearance rate calculated using S9 data was 10‐fold higher than that determined using hepatocytes, possibly due to a diffusion limitation on cellular uptake. Generally, however, there was good agreement between calculated in vivo intrinsic clearance rates obtained using either in vitro test system. These results suggest that both systems can be used to improve bioaccumulation assessments for fish, particularly when vitro rates of activity are relatively high, although additional work is needed to determine if the chemical domain of applicability for each system differs. Environ Toxicol Chem 2017;36:463–471. Published 2016 SETAC. This article is a US government work and, as such, is in the public domain in the United States of America.